Pengaruh Viral Marketing, Brand Image, dan E-WOM terhadap Keputusan Pembelian Produk Skincare Skintific - Jenifer Pesik; Suhaji Suhaji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of viral marketing, brand image, and electronic word of mouth (E-WOM) on the purchasing decisions of Skintific skincare products among TikTok marketplace users. This research is expected to contribute theoretically to the development of digital marketing management and serve as a practical reference for companies in optimizing their marketing strategies on social media. This research employs a quantitative approach using a survey method. The research sample consists of 100 respondents who are TikTok marketplace users who have purchased Skintific products, selected through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression, which included validity tests, reliability tests, classical assumption tests, and hypothesis testing (t-test and F-test). The results indicate that partially, viral marketing, brand image, and E-WOM each have a positive and significant influence on purchasing decisions. Simultaneously, the three variables are proven to have a significant effect, with a contribution of 70.9% toward purchasing decisions. These findings confirm that a combination of viral marketing strategies, a strong brand image, and positive online reviews are the primary determinants in driving consumer purchasing decisions in the TikTok marketplace.